INCOME AND EFFICIENCY OF KASTURI VOOR OOGST TOBACCO FARMING IN BANYUGLUGUR DISTRICT, SITUBONDO REGENCY - Agus Supriono; Dwi Robiul Riskiyah; Rizky Yanuarti; Julian Adam Ridjal; Soetriono Soetriono; Rena Yunita Rahman; Julita Hasanah; Cindera Rosa Damascena (Undana Press, 2026)
Kasturi Voor Oogst tobacco produced in Banyuglugur District, Situbondo Regency, is widely recognized for its excellent quality, making it relatively preferred by several tobacco supplier companies that provide raw tobacco material for cigarette factories in Indonesia. However, annual production has tended to decline continuously. Therefore, it is important to examine the actual income and efficiency of Kasturi Voor Oogst tobacco farming. It is also necessary to determine the condition of farming income and efficiency under possible changes, namely declining production, decreasing product prices, and increasing production costs. The analytical approaches used in this study were farm income analysis (π), R/C ratio analysis, and sensitivity analysis. The results show that Kasturi Voor Oogst tobacco farming is profitable and efficient, both for farmers who enter into partnership cooperation with tobacco supplier companies and for farmers who do not. When a decline in production and output prices of up to 15%, as well as an increase in production costs of up to 15%, are taken into account, farming remains profitable and efficient.